A High Incidence of Selection on Physiologically Important Genes in the Three-Spined Stickleback, Gasterosteus aculeatus - Shimada, Yukinori; Shikano, Takahito; Merilä, Juha (Molecular biology and evolution, 2011)
Genome scan approaches to detect footprints of directional selection in the genomes of wild animal and plant populations have become popular tools to study local adaptation and speciation at the molecular level. Most studies thus far have used random molecular markers and found footprints of directional selection at, on average, 5% (range: 1–15%) of the examined loci. We focused on physiologically important genes that exhibit transcriptional responses to specific environmental or developmental conditions and assessed if these genes have been subject to directional selection and are responsible for local adaptation in the three-spined stickleback (Gasterosteus aculeatus). Using microsatellite markers located within or closely linked to (<6 kb) target genes, we investigated footprints of directional selection for 157 genes with known physiological functions in three marine and six freshwater populations. A high incidence (16.6%) of footprints of directional selection for these genes was revealed by four different outlier tests. In a subset of four populations screened with both physiologically important and random genes, footprints of directional selection were more frequent in physiologically important genes (13.4%) as compared with random genes (2.4%). In general, our findings indicate strong selective pressures on physiologically important genes, suggesting that these genes have significant functions in evolutionary adaptation to environmental heterogeneity.